The agrarian question in the neoliberal era primitive accumulation and the peasantry - Patnaik, Utsa; Moyo, Sam (Pambazuka Press, 2011)
Capitalism manoeuvres to control agricultural production in developing countries where neoliberalism has already decreased food security. Unless the land rights of small producers are defended, their active resistance will undermine political stability.